Carbon‐ion radiotherapy for urological cancers. (12th June 2022) - Ishikawa, Hitoshi; Hiroshima, Yuichi; Kanematsu, Nobuyuki; Inaniwa, Taku; Shirai, Toshiyuki; Imai, Reiko; Suzuki, Hiroyoshi; Akakura, Koichiro; Wakatsuki, Masaru; Ichikawa, Tomohiko; Tsuji, Hiroshi
Abstract: Carbon‐ions are charged particles with a high linear energy transfer, and therefore, they make a better dose distribution with greater biological effects on the tumors compared with photons and protons. Since prostate cancer, renal cell carcinoma, and retroperitoneal sarcomas such as liposarcoma and leiomyosarcoma are known to be radioresistant tumors, carbon‐ion radiotherapy, which provides the advantageous radiobiological properties such as an increasing relative biological effectiveness toward the Bragg peak, a reduced oxygen enhancement ratio, and a reduced dependence on fractionation and cell‐cycle stage, has been tested for these urological tumors at the National Institute for Radiological Sciences since 1994. To promote carbon‐ion radiotherapy as a standard cancer therapy, the Japan Carbon‐ion Radiation Oncology Study Group was established in 2015 to create a registry of all treated patients and conduct multi‐institutional prospective studies in cooperation with all the Japanese institutes. Based on accumulating evidence of the efficacy and feasibility of carbon‐ion therapy for prostate cancer and retroperitoneal sarcoma, it is now covered by the Japanese health insurance system. On the other hand, carbon‐ion radiotherapy for renal cell cancer is not still covered by the insurance system, although the two previous studies showed the efficacy. In this review, we introduce the characteristics, clinical outcomes, and perspectives of carbon‐ion radiotherapy and our efforts to disseminate the use of this new technology worldwide.